Hubungan Tingkat Pengetahuan Terhadap Perilaku Swamedikasi Maag Mahasiswa Prodi Farmasi (S-1) Universitas Jnederal Achmad Yani Yogyakarta - Windi Astuti; Larasati, Niken; Rosita, Melia Eka (JOURNAL OF PHARMACEUTICAL (JOP), 2024)
Background: Gastritis is a disease that arises due to damage or infection in the stomach and then attacks stomach acid with the characteristics of heartburn, nausea and quick satiety. Gastritis is a common disease that can be treated with self-medication or self-medication with drugs without a doctor's prescription. The level of knowledge in self-medication plays an important role in order to obtain maximum therapeutic results. Self-medication behavior is formed from external responses or stimuli carried out by a person doing self-medication in treating the disease they are experiencing. Research purposes: The purpose of this study was conducted to determine the relationship between the level of knowledge and self-medication behavior for gastric ulcer students of the Pharmacy Study Program (S-1) Jenderal Achmad Yani University, Yogyakarta. Research methods: This research method uses a type of analytic survey with a cross-sectional research design. The sampling technique used is purposive sampling technique. The sample used was 82 respondents. Research result: The results of the study show that 63 respondents (76,8%) have good knowledge and 19 respondents (23,2%) have enough knowledge. The behavior of ulcer self-medication shows that 59 respondents (72,0%) have good behavior and 23 respondents (28,0%) have enough behavior. Conclusion: Data analysis used the Chi Square correlation test and obtained a significance value of 0,000 (Asymp.Sig (2-sided) <0.05) which indicates that there is a relationship between knowledge of self-medication behavior for ulcers in Pharmacy Study Program students (S-1) General Achmad Yani University, Yogyakarta.